(untitled) (Heritage, 2020)
Тhe curriculum is the starting point for effective teaching planning. The outcome of the teaching process in secondary vocational schools depends, to a large extent, on the conception of the curriculum prescribed by state bodies, which is the case with most countries of the Western Balkans, including Serbia. The paper deals with the issue of English for specific purposes in secondary vocational schools, the representation of English for specific purposes in the curriculum of secondary vocational schools in Kosovo and Metohija, which are under the jurisdiction of the Ministry of Education, Science and Technological Development of the Republic of Serbia. The research describes approaches to curriculum development and planning for English for specific purposes. The analysis of plans and programs for the English language showed that the needs of students of vocational secondary schools of technical orientation in terms of English for specific purposes are not fully met. The research defines the components that are important to include in order to harmonize goals, forms and educational activities that will improve students’ knowledge and prepare them for future professional roles.